The Role of Flavonoids in Mitigating Oxidative Stress: Mechanisms, Applications and Therapeutic Potential (Asian Journal of Pharmaceutics (AJP), 2025)
Oxidation is a fundamental aspect of aerobic life processes, involving a reaction in which either electrons orhydrogen are transported from an element to an oxidizing mediator, resulting in the creation of free radicals.Oxidative stress is generally a result of an inequity between reactive oxygen species production and theantioxidant level of a biological system. This is the key factor in the advancement of numerous pathologicalconditions, such as cardiovascular and neurodegenerative disorders. Flavonoids are an extraordinary class ofplant secondary metabolites that have been traditionally utilized as medicines, offering scientifically validatedtherapeutic benefits. The use of phytochemicals, particularly flavonoids, in the prevention and treatment ofdiseases is well recognized. Fruits, as well as green vegetables, are natural sources of flavonoids. For humans,recent studies have primarily concentrated on the beneficial effects of flavonoids on well-being. The flavonoidsare classified into six different subclasses based on their ring structure. In the present review work, we havefocused on the effect of flavonoids and its mechanism in reducing oxidative stress and, ultimately, variousdisorders. Flavonoids mainly produce their antioxidant effect through neutralizing free radicals, inhibitingenzymes responsible for the generation of free radicals, formation of chelates with metal ions, and stimulatingthe internal antioxidant defense system. We have also highlighted the therapeutic potential of flavonoids asfuture therapeutic agents.